Compulsory licensure as a cost-containment measure for essential medicines: a comparative study of South Africa, the Russian Federation and the People's Republic of China - Mabote, Keneilwe Lynette (Intellectual Property Research Unit, 2020)
This minor dissertation investigates alternative compulsory licencing (CL) policy approaches for the South African context. The purpose is to support the country's aspirations to reform certain components of its intellectual property (IP) regime, ensuring alignment with the country's development prerogatives. Homing in on technical barriers with the operationalisation of the existing CL mechanism; this paper investigates remedial recommendations to support South Africa's reform efforts. The paper also hopes to gauge whether it is feasible to leverage compulsory licensure as a cost-containment tool to circumvent price dominance in the sale of essential pharmaceutical commodities. The South African Patents Law provides for CL under three grounds. These are dealt with in chapter 2. The abuse of patents rights as a result of excessive pricing is one of these grounds. Yet, attempting to use this provision abuse of patents rights is procedurally and administratively cumbersome. This is notwithstanding the litigation costs. The 2018 national IP Policy aspires to reform the CL policy to ensure that it is a 'workable mechanism'. A comparative analysis of the CL policy landscapes in the People's Republic of China (PRC) and the Russian Federation will be taken to inform South Africa's discourse. These two countries are strategic because they have either reformed and/ or in the process of renovating their intellectual property rights (IPR) landscapes and both have interesting approaches to the way in which they have reformed their CL mechanisms. The findings of this paper reveal that Russia and China have undertaken extensive IPR reforms over the last three decades. They have both taken different policy approaches in adapting their CL instruments. Russia's CL reform proposals are underway and aim to advance a CL mechanism that can effectively regulate the abuse of patents, especially for essential pharmaceutical commodities. China has installed specific Implementing Measures which offer policy guidance on the applicability CLs. In the case study of China, the Measures imposed are not necessarily advanced as cost-containment tools. Rather they support the country's pharmaceutical agenda. The recommendations in this paper offer interesting insights to the feasibility exercises that will be advanced in South Africa's IPR reform process.